Food movements in Germany: analysis of actors in the socio-ecological transformation of the food system - Zentgraf, Lea; Campos Motta, Renata (Food for justice working paper series, 2024)
Around the world, social movements are protesting against the corporate food regime (Friedmann & McMichael, 1989), denouncing the injustices associated with its structural dynamics of neoliberal capitalism, patriarchal domination, racism, coloniality, epistemic violence, and anthropocentric exploitation (Motta, 2021b; Holt Giménez & Shattuck, 2011; Holt-Gimenez & Patel, 2012). Many food movements are calling for a socio-ecological transformation and creating alternative forms to produce, share, prepare, consume and dispose of food, based on relations of care, solidarity and respect. In their heterogeneity, they provide a good analytical lens to explore the multiple and intersectional dimensions of food inequalities denounced and the directions of change desired by organized movements from civil society (Motta, 2021a). But which are the food movements that mobilize for a socio-ecological transformation of food politics in Germany? What are the main dimensions and intersections of inequalities addressed by them?
Gesehen am 10.06.2024
Keywords: Graue Literatur